THE IMPACT OF SHIFT IN TAX REGULATIONS ON INDIVIDUAL TAXPAYER COMPLIANCE IN BOGOR RAYA - Raden Muhammad Jiddan Aziz; Riski Putri Kusumaningsih; Ni Luh Putu Ayu Rediastuti S; Ari Irawan; Ginanda Rizky Amalia (Finance : International Journal of Management Finance, 2024)
This research investigates the impact of factors such as tax education, digital services, tariffs and tax incentives on individual taxpayer compliance in Bogor Regency, especially during the COVID-19 pandemic. In response to the economic challenges faced, the government provides tax incentives, as regulated in Minister of Finance Regulation Number 9/PMK.03/2021. The results of data analysis from 112 respondents show that tax education has a significant effect on taxpayer compliance, while digital services do not have a significant impact. On the other hand, tax rates and incentives play an important role in improving compliance. With an R2 value of 65.4%, this research provides in-depth insight into the factors that influence tax compliance in the region. It is hoped that these findings can become the basis for policies to increase taxpayer compliance and support economic recovery.